Phenrica littoralis (Bechyné, 1955) (Coleoptera: Chrysomelidae) a potential candidate for the biological control of alligator weed, Alternanthera philoxeroides (Martius) Grisebach (Amaranthaceae): redescription of the adult, first description of immature stages, and biological notes - Cabrera, Nora Clara (2013)
Flea beetles of alligator weed, Alternanthera philoxeroides (Martius) Grisebach (Amaranthaceae), were collected in Argentina, Uruguay, Paraguay, and Brazil. Species in the genera Disonycha Chevrolat, Agasicles Jacoby, Systena Chevrolat and Phenrica Bechyné were frequently found on this weed. Phenrica littoralis (Bechyné) was the most abundant within this genus. The male is described and the holotype female is redescribed adding new diagnostic characters of the mouthparts, hind wings, metendosternite, and male and female genitalia. Larva and pupa are described and illustrated for the first time providing data for future phylogenetic studies in the subtribe Disonychina.